Literacy Quebec Newsletter - Literacy Quebec (LQ) (2024)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2023)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2023)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2023)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2023)

Consultation prébudgétaire de Alphabétisation Québec 2023-2024 déposé au ministre des Finances du Québec et au ministre responsable des Relations avec les Québécois d’expression anglaise - Literacy Quebec (LQ) (2023)
Alphabétisation Québec/Literacy Québec est un regroupement national qui compte 15 organismes d’alphabétisation populaires. Fondé en 1980, il est accrédité au Programme d’action communautaire sur le terrain de l’éducation (PACTE) et reçoit un soutien financier pour appuyer sa mission globale de la part du ministère de l’éducation ainsi que du Secrétariat aux relations avec les Québécois d’expression anglaise. Le regroupement mène des actions pour conscientiser le public aux réalités de l'analphabétisme et pour promouvoir des opportunités d’apprentissage tout au long de la vie. Alphabétisation Québec offre du soutien, de l’accompagnement et de la formation continue à ses groupes membres. Ceux-ci sont des milieux de vie et des lieux de formation pour les adultes et les familles de toutes origines qui désirent acquérir, rehausser ou maintenir leurs compétences de base sur le plan de la lecture, l’écriture, la numératie ou la littératie numérique. Ils ont développé une approche unique d’éducation non formelle et informelle qui vise l’autonomisation et l’inclusion des personnes et qui est adaptée au rythme d’apprentissage des participants.

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2023)

2022-2023 Activity Report - Literacy Quebec (LQ) (2023)

Literacy Quebec Newsletter : Special Edition - Literacy Quebec (LQ) (2023)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2022)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2022)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2022)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2022)

COVID-19 Survey Report II - Literacy Quebec (LQ) (2021)
While the pandemic has forced a lot of swift changes, the majority of Literacy Quebec's member organizations have been able to adapt. In fact, 8 out of 9 respondents claimed to have successfully transitioned at least some of their programs and services online. However, while most organizations were able to move to some type of online- learning model, a select few reported having no available tutors/volunteers. Some of the reasons ranged from a lack of interest (i.e. volunteers originally signed up to interact with others in person), or a lack of confidence in using technology.

Activity Report - Literacy Quebec (LQ) (2021)

Family Literacy Toolkit - Literacy Quebec (LQ) (2021)

Activity Report 2019-2020 - Jamaica Association of Montreal (JAM) (2020)

Annual Report 2019/2020 : 40th Anniversary Edition - Literacy Quebec (LQ) (Literacy Quebec, 2020)

Celebrating 40 Years - Literacy Quebec (LQ) (2020)
The year was 1980 and the world was undergoing massive change. CNN launched, the Rubik’s cube went on sale and the Iran-Iraq war began. Closer to home, Quebecers voted in a sovereignty referendum to remain part of Canada, while the sports scene saw the Montreal Canadiens fail in their quest for a fifth consecutive Stanley Cup. But something else historic was also brewing in the province that year: Laubach Literacy Canada-Quebec (LLC-Q), the forerunner of Literacy Volunteers of Quebec, now known as Literacy Quebec.

Annual Activity Report : June 1, 2018 - May 31, 2019 - Literacy Quebec (LQ) (2019)

Annual Activity Report : June 1, 2017 - May 31, 2018 - Literacy Quebec (LQ) (2018)
Literacy Quebec provided ongoing support to its members by offering training and assistance via web, email and telephone. The LQ staff fielded and responded to 950+ enquiries and concerns from its membership. They also sent out 30 email updates throughout the year. Members were brought together once in person and once via web-conference for professional developments and networking opportunities.
Keywords: Official Language Minority Community (OLMC)

Annual Activity Report : June 1, 2016 - May 31, 2017 - Literacy Quebec (LQ) (2017)
Literacy Quebec continued to provide support to its members by offering training and assistance via web, email and telephone. Members were brought together once in person and once via conference call for professional development and networking opportunities. Through a PACTE funded project, Literacy Quebec was able to develop tools to strengthen its network. The project allowed us to examine new ways of promoting literacy and explaining the issues surrounding low literacy to the general public. The project also enabled the organization to engage more volunteers and pilot a database to track volunteers, supporters, members, etc.

Annual Activity Report : June 1, 2015 - May 31, 2016 - Literacy Quebec (LQ) (2016)
Literacy Quebec continued to provide support to its members by offering training and assistance via web, email and telephone. Members were brought together once in person and once online via web-conference for professional development sessions and networking opportunities.

Letter to the Minister of Education, Higher Education and Research - Legault, Margo; Brassard, François (2016)

Lettre au ministre de l’Éducation, de l’Enseignement supérieur et de la Recherche - Legault, Margo; Brassard, François (2016)

Annual Activity Report : June 1, 2013 - May 31, 2014 - Literacy Quebec (LQ) (2014)

PACTE Project 2013-2014 : The Power of an Online Presence, a Skill to be Harnessed. - Literacy Quebec (LQ) (2014)
The following project has been completed by Literacy Quebec by a grant from Opération Projets PACTE As a provincial organization, Literacy Quebec’s mandate is to support community-based literacy organizations that provide service to English-speaking adults in Quebec, through training, networking and professional development.

Western Quebec Literacy Council: Annual Report: 2013-2014 - Western Quebec Literacy Council (2014)

Annual Activity Report : June 1, 2012 to May 31, 2013 - Literacy Quebec (LQ) (Literacy Quebec, 2013)

A Health Literacy Tool Kit for Healthcare Providers : Improving Communication with Clients - Strickland, Kate (Literacy Volunteers of Quebec, 2011)

Pas de talents à perdre : priorité à l’alphabétisation - Charest, Jean; David, Françoise; Dumont, Mario; Khadir, Amir; Marois, Pauline; Rainville, Guy; La Coalition pour l’alphabétisation (2008)

Bridging the Gap Meeting - Literacy Quebec (LQ) (2007)

Literacy Resource Directory : Prevention Activities in Quebec - Seys, Wendy (Literacy Volunteers of Quebec, 2004)

Competency-Based Progress Assessment Skills for Life-long Learning - Literacy Quebec (LQ)

Family Literacy Toolkit : Resources, Planning Guide, Best Practices - Literacy Quebec (LQ)
Literacy Quebec is a network that connects and represents community-based literacy organizations to empower people, impact lives and build a stronger society. We envision a Quebec where everyone has the literacy skills they need to live a fully engaged life.

L’alphabétisation, c'est beaucoup plus que l'abc : C’est un enrichissement pour nos communautés - Literacy Volunteers of Quebec